The Influence of Grit and Growth Mindset in Maintaining the Sustainability of Small and Medium Enterprises in Kupang City - Indawati Nino; Hamzah Nazarudin; Maria Dola (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2025)
This study aims to examine the influence of grit and growth mindset on entrepreneurial success in Micro, Small, and Medium Enterprises (MSMEs) in Kupang City. In the context of the challenges faced by MSME actors, especially in the Eastern Indonesia region, resilient character and a developing mindset are important factors in determining the resilience and success of the business. Grit, which reflects perseverance and consistency towards long-term goals, as well as a growth mindset, which is the belief that skills can be developed through effort and learning, are seen as able to strengthen entrepreneurial resilience. This study uses a quantitative approach with a survey method on MSME actors, as well as data analysis through PLS-SEM. The results of the study are expected to make a theoretical contribution to the literature on entrepreneurship and positive psychology, as well as the basis for the formulation of MSME empowerment strategies based on strengthening character and mindset, especially in areas with limited resources such as Kupang City.